DIRECT MEASUREMENTS OF THE GENERAL MAGNETIC FIELD ON THE SOLAR-LIKE STARS - Plachinda, S. I.; Johns-Krull, C. M.; Tarasova, T. N. (Одеські астрономічні публікації, 2017)
We report the high-precision spectropolarimetric measurements of the general magnetic field (GMF) on a solar-like star 61 Cyg A. The magnetic field shows periodic variations due to stellar rotation with a period of Pmf = 36.59 ± 0.18 days. The net longitudinal magnetic field of 61 Cyg A varied from –13 G to + 4 G. The conclusion was made that the nonaxisymmetric large-scale magnetic field (original magnetic field - OMF) on the surface of the Sun and solar-like stars ξ Boo A and 61 Cyg A is present in addition to toroidal and axisymmetric poloidal fields, which are produced by dynamo. The characteristics of the OMF point to a presence of a global magnetic field in the star radiative interior and re internal field properties on the surface. The birth and formation of magnetic active regions (ARs) on the surface of the solar-like star 61 Cyg A has been registered. The numerical simulations were compared with magnetic measurements, and lead us to the conclusion about the presence on 61 Cyg A of more strong magnetic of ARs (∼ 1023 – 1024 Mx) than on the Sun. These ARs can be formed at the same latitudes as on the Sun.